Thinking about Normativity: Ralph Wedgwood on 'Ought' - Muijnck, Wim de (Journal of moral philosophy, 2010)
Abstract Ralph Wedgwood's The Nature of Normativity provides a theory about the semantics, metaphysics, and epistemology of normative judgments, taken to be judgments of the form 'I ought to '. The theory is based on the principle of Normative Judgment Internalism, and the principle that 'the intentional is normative'. I argue, first, that by being merely about oughts, Wedgwood's account leaves out one essential constituent of normativity: value. Secondly, I argue that mainly because of this, the account faces a serious issue of relevance.